Utilization of E-learning by Agricultural Students of Public Higher Institutions in Southwest of Nigeria - Oluwasusi, Sola Joshua; Olagunju, Oluwatoyin; Akinbola, Adeyose Emmanuel; Yekinni, Oyedeji Taofeeq (International Journal of Environment, Agriculture and Biotechnology, 2021)
This study aimed at determining the utilization of e-learning by agricultural students’ of public higher institutions in the Southwest of Nigeria. A multistage sampling procedure was used to select 300 respondents from the higher institutions. Students were mostly female with a mean age of 22.4 years and with majority enrolled in undergraduate programmes. Respondents had a low usage of e-learning due to low awareness and knowledge level, complexity of technology and inadequate e-learning infrastructures in their schools. A significant relationship existed between constraints, awareness, knowledge, and utilization of e-learning. The regression analysis carried out in this study resulted in R-square of .957. These findings indicate that about 95.7% of variance in the level of usage of e-learning is explained by awareness, knowledge and different constraints. The study recommends that efforts should be geared towards encouraging students to integrate e-learning usage in their academic activities by providing e-learning infrastructures and easy access through competent e-learning personnel.